Intraoperative Assessment of Sentinel Lymph Nodes in Breast Cancer Patients Post-Neoadjuvant Therapy. (19th July 2019) - Wong, Willard; Rubenchik, Illana; Nofech-Mozes, Sharon; Slodkowska, Elzbieta; Parra-Herran, Carlos; Hanna, Wedad M.; Lu, Fang-I
Background: Shift toward minimizing axillary lymph node dissection in patients with breast cancer post neoadjuvant therapy has led to the assessment of sentinel lymph nodes by frozen section intraoperatively to determine the need for axillary lymph node dissection. However, few studies have examined the accuracy of sentinel lymph node frozen section after neoadjuvant therapy. Our objective is to compare the accuracy of sentinel lymph node frozen section in patients with breast cancer with and without neoadjuvant therapy and to identify features that may influence accuracy. Design: We identified 161 sentinel lymph node frozen section from 77 neoadjuvant therapy patients and 255 sentinel lymph node frozen section from 88 non-neoadjuvant therapy patients diagnosed between 2010 and 2016 in 2 institutions. The frozen section diagnoses were compared to the final diagnoses, and clinicopathologic data were analyzed. Results: The sensitivity, specificity, and accuracy of frozen section analysis were comparable between neoadjuvant therapy patients and non-neoadjuvant therapy patients (71.9% vs 50%, 100% vs 100%, and 88.3% vs 81.8%). Nine (11.7%) of 77 neoadjuvant therapy patients had discordant results, most often due to undersampling (tumor absent on frozen section slide). Four of these patients subsequently underwent axillary lymph node dissection. Discordant results (all false negatives) were significantly more likely in neoadjuvant therapy patients with Estrogen Receptor-positive/HER2-negative status, and in sentinel lymph node with pN1mic and pN0i+ deposits; age, preneoadjuvant therapy lymph node status, histotype, nuclear grade, tumor size, and response to neoadjuvant therapy showed no significant differences. For non-neoadjuvant therapy cases, large tumor size, lobular histotype, and sentinel lymph node with pN1mic and pN0i+ were associated with false-negative frozen section assessment. Conclusion: Sentinel lymph node frozen section diagnosis post-neoadjuvant therapy has comparable sensitivity, specificity, and accuracy to the sentinel lymph node frozen section diagnosis in the non-neoadjuvant therapy setting.